1982
DOI: 10.1056/nejm198211253072202
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Coronary Reserve

Abstract: The pathogenesis of angina pectoris in patients with aortic stenosis and normal coronary arteries remains uncertain. Using a specially designed Doppler probe, we measured the maximal velocity of coronary blood flow in the left-anterior descending coronary artery at the time of elective open-heart surgery in 14 patients with aortic stenosis and left ventricular hypertrophy (13 had angina) and in 8 controls without left ventricular hypertrophy. The ratio peak velocity of coronary blood flow, after a 20-second oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 525 publications
(42 citation statements)
references
References 24 publications
0
40
1
1
Order By: Relevance
“…[1][2][3][4] They include impaired cardiac performance and coronary hemodynamics and ventricular fibrosis. [5][6][7][8][9] In a recent study involving normotensive and spontaneously hypertensive rats (SHRs), aged 22,35 and 65 weeks, we demonstrated that associated with aging per se there were progressive impairments in coronary hemodynamics with increased myocardial collagen deposition in both strains. 9 These changes were more pronounced in hypertensive rats at any age, as if hypertension might have induced premature aging alterations of cardiovascular system.…”
mentioning
confidence: 99%
“…[1][2][3][4] They include impaired cardiac performance and coronary hemodynamics and ventricular fibrosis. [5][6][7][8][9] In a recent study involving normotensive and spontaneously hypertensive rats (SHRs), aged 22,35 and 65 weeks, we demonstrated that associated with aging per se there were progressive impairments in coronary hemodynamics with increased myocardial collagen deposition in both strains. 9 These changes were more pronounced in hypertensive rats at any age, as if hypertension might have induced premature aging alterations of cardiovascular system.…”
mentioning
confidence: 99%
“…This was also the case in Park's study, 11 as well as in other studies using quantitative coronary angiography. [13][14][15] It is important to recognize that myocardial blood flow is dependent on many other factors besides proximal coronary stenosis, such as aortic pressure, 12 diffuse coronary atherosclerosis, 16 microvascular function, 17 and collateral blood flow. 12 All these factors are more difficult to measure by coronary CTA.…”
Section: See Article By Dey Et Almentioning
confidence: 99%
“…On the other hand, the increase in the diastolic pressure will result in increased endocardial compression of the coronary arteries and decease in coronary perfusion. Those two factors (decrease the myocardial perfusion time and decrease coronary blood flow) in addition to the increased oxygen demand of the hypertrophied ventricle will result in subendocardial ischemia, which may result in symptoms similar to angina pectoris and LV dysfunction (Marcus, Doty, Hiratzka, Wright, & Eastham, 1982).…”
Section: Pathophysiology and Hemodynamicsmentioning
confidence: 99%